Peran Seni Islam dalam Film Pendek Nussa “Belajar Jujur” Sebagai Media Dakwah Pembinaan Akhlak - Viki Fadhilah; Meti andani; Sri Yulianti; Yazida Ichsan (Busyro : Jurnal Dakwah dan Komunikasi Islam, 2022)
Art education in Islam is very important to be instilled in children, apart from being a medium for conveying the messages implied in it, art in Islam also gives an impression that has elements of beauty and harmony, so there is a need for learning media in improving education through the art of Islamic education. The purpose of this study was focused on fostering students' morals through the short film Nusa Rara entitled "Honest Learning" as a medium of da'wah in the art of Islamic education. This research was conducted by analyzing the short film Nusa Rara to be used as a medium for Islamic da'wah art education so that it can be used as an example or role model for the audience, especially if it is associated with education, students are expected to take lessons from the film. The method used is descriptive qualitative method and analysis. The results of this study indicate that the Nusa Rara film entitled "Learning Honestly" can have a good influence on the students, of course, and can make a good influence on the audience to always be honest in everything, especially when taking exams.